2022
DOI: 10.1021/acsami.2c10728
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Multifunctional Peptide-Conjugated Gene Carrier/miRNA-218 Complexes from Monodisperse Microspheres for Bone Regeneration

Abstract: MicroRNAs (miRNAs) play a pivotal role in regulating gene expression and are considered new molecular targets in bone tissue engineering. However, effective delivery of miRNAs to the defect areas and transfection of the miRNAs into osteogenic progenitor cells has been an obstacle in the application. In this work, miRNA-218 (miR-218) was used as an osteogenic miRNA regulator, and a multifunctional peptide-conjugated gene carrier poly­(lactide-co-glycolide)-g-polyethylenimine-b-polyethylene glycol-R9-G4-IKVAVW (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…MicroRNAs (miRNAs), a small molecular RNA family, are short noncoding RNA sequences that post‐transcriptionally regulate the expression of mRNAs by targeting their 3′‐UTR and participate in various vital processes (Gao et al., 2022; Huang et al., 2019; Jiang et al., 2022; Wang et al., 2021). Previous studies have demonstrated the involvement of miR‐218 in the osteogenic differentiation of MSCs (Karimi et al., 2020; Li, Deng, et al., 2022; Li, Hu, et al., 2021; Shi et al., 2018). Our results confirmed that the odonto/osteogenic differentiation of SCAPs was repressed by a miR‐218‐5p mimics but promoted by a miR‐218‐5p inhibitor.…”
Section: Discussionmentioning
confidence: 98%
“…MicroRNAs (miRNAs), a small molecular RNA family, are short noncoding RNA sequences that post‐transcriptionally regulate the expression of mRNAs by targeting their 3′‐UTR and participate in various vital processes (Gao et al., 2022; Huang et al., 2019; Jiang et al., 2022; Wang et al., 2021). Previous studies have demonstrated the involvement of miR‐218 in the osteogenic differentiation of MSCs (Karimi et al., 2020; Li, Deng, et al., 2022; Li, Hu, et al., 2021; Shi et al., 2018). Our results confirmed that the odonto/osteogenic differentiation of SCAPs was repressed by a miR‐218‐5p mimics but promoted by a miR‐218‐5p inhibitor.…”
Section: Discussionmentioning
confidence: 98%
“…Since periodontal bone resorption generally forms irregular alveolar bone defects, injectable biomaterials that can easily fill any shape of defects are more attractive than conventional pre‐formed 3D biomaterials. [ 9 ] Hydrogels are injectable biomaterials and have been tested for bone formation. [ 10 ] However, the limitations of hydrogels include the inferior mechanical property and poor integration with surrounding tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive surgery-based regenerative therapy is an attractive strategy for bone defect treatment due to its advantages of smaller incisions, faster recovery, and fewer complications in comparison with traditional surgery. , Injectable biomaterials can fill defects with irregular shape and create a local microenvironment that is conducive to tissue regeneration when they are properly prepared and functionalized to accelerate the repair process . Recently, biodegradable microspheres have emerged as one of the most promising injectable microscaffolds with the following features: (1) diverse physical morphology and chemical composition, (2) higher specific surface area than bulk scaffolds, and (3) flexibility in assembly. Microspheres have formed a platform technique to improve the regeneration of injured bone tissue via providing diverse biochemical and biophysical cues for cell fate modulation. …”
Section: Introductionmentioning
confidence: 99%